GAMBARAN NILAI GIZI MAKANAN YANG DIKONSUMSI OLEH REMAJA OBESITAS DI SEKOLAH - Ulfa Raudha; Zahtamal "; Yanti Ernalia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTObesity currently more occurs in adolescence. The purpose of this study was to determinate the content of carbohydrates, protein, fat, energy content and energy intake in obese students at the school. This is a descriptive quantitative study. The sample was food that often consumed by obese students in caffetaria at SMA N 4 Pekanbaru. The result of this study was carbohydrate content for pisang goreng, sandwich, bakso goreng, nasi goreng, and batagor were lower than Tabel Komposisi Pangan Indonesia (TKPI). The protein content for sandwich, nasi goreng, bakso goreng, and batagor were higher than TKPI, the protein content for pisang goreng was lower than TKPI. The fat content for pisang goreng, sandwich, nasi goreng, and batagor were higher than TKPI, the fat content for bakso goreng was lower than TKPI. The highest energy intake of obese students in the school was 1.334,7 kcal (62,8% AKG) and the lowest was 597,3 kcal (28,1% AKG). One of the recommendation is to balance the composition of carbohydrates, protein, and fat in a food serving.Keywords: Carbohydrates content, protein, fat, energy content, energy intake